Percepção do portador de deficiência física com relação à qualidade dos espaços de circulação urbana - Orlandi, Silvia Cristina (2003)
This research presents the results of a survey that was carried out with wheelchair users and mobility-impaired people. The focus of the survey was in identifying the importance of the physical and environmental variables that characterize the sidewalks according to the aspects of comfort, safety and environmental quality. Initially, the identification and organization of the variables were obtained by an iterative survey method with specialists in the areas of engineering, architecture, urban planning, physical therapy, occupational therapy and human mobility. This process resulted in a consensus regarding the variables that can be related to the aspects of comfort, safety and environmental quality. The characteristics selected by the specialists, as measures of the quality of the sidewalks were included in a survey with wheelchair users and mobility-impaired people in order to evaluate the importance attributed by them to each of the characteristics. It was found that their perception not always matches the hierarchy of importance of the variable as evaluated by the specialists. The objective population priorizes the physical characteristics of the sidewalks that offer a minimum of movement condition, rather then those that offer additional quality conditions in the aspects of comfort, safety and environmental quality.